Idosos em Boa Vista: Análise Social / 2000 - BONFIM, MARIA GEOVANÍ; VALE, ANA LIA FARIAS; MULLER, CRISTIANO; NASCIMENTO, DAYANE; GRAZIELLY, GEÓRGIA; RODRIGUES, ROBSON (Textos e Debates, 2012)
Não consta em edição publicada.